AD, Volume 36, n° 3 & 4, 2011 - Full Issue - Journal System (Africa Development, 2021)
Papers published in this issue were first presented at an international conference on the “Youth and the Global South” under the theme: “Religion, Politics and the Making of Youth in Africa, Asia and the Middle East” convened by African Studies Centre (ASC) Council for the Development of Social Science in Africa (CODESRIA), Institute for the Study of Islam and the Middle East (ISIM), and International Institute for Asian Studies (IIAS). Contents Introduction: Ideologies of Youth Rijk van Dijk, Mirjam de Bruijn, Carlos Cardoso & Inge Butter ........................... 1 Padvinders, Pandu, Pramuka: Youth and State in the 20th Century Indonesia Pujo Semedi ................................. 19 Institutionalising Terror in the Name of Religion and Polity: The Nigerian Youth and the Cosmos of Violence Amidu Sanni............................ 39 African ‘Youth’ since Independence: Notes on a Bibliographic Overview, 1990 to 2005 Fiona Klein Klouwenberg & Inge Butter ...........55 Seeing the State through Youth Policy Formation: The Case of the State of Jharkhand Kathinka Sinha-Kerkhoff.......................... 67 Mayi-Mayi: Young Rebels in Kivu, DRC Luca Jourdan....................... 89 Hip-Hop and Bongo Flavour Music in Contemporary Tanzania: Youths’ Experiences, Agency, Aspirations and Contradictions Maria Suriano ..............................113 Youth Religiosity and Moral Critique: God, Government and Generations in a Time of AIDS in Uganda Catrine Christiansen ..........................127